Estudo da persea americana no controle do diabetes mellitus: revisão sistemática - SILVA, Vivian Brito (2021)
Background: Diabetes mellitus (DM) is a prevalent disease that represents one of the greatest challenges for public health. The use of medicinal plants has been used frequently in folk medicine and some in the control of diabetes, such as Persea americana, widely used in developing countries. Thus, this work aims to collect scientific knowledge about the plant species P. americana in the control of DM through a systematic review. Methods: This is a systematic review of in vivo and in vitro studies according to recommendations of the PRISMA protocol,carried out by complying with the following steps: 1) elaboration of the guide question occurred from the acronym PICO (P - Population and/or Problem, I - Intervention, C - Comparison andO - Outcome) with definition of the descriptors; 2) sampling (selection of articles) according to inclusion/exclusion criteria; 3) search of the articles in the databases Scopus, PubMed/MEDLINE and VHL (BIREME); 4) sampling (selection of articles); 5) definition of the information to be extracted from the reviewed papers; 6) synthesis of the knowledge evidenced in the analyzed articles. Results: Of the 12 selected articles, eight were experimental studies in vivo and 4 experimentalstudies in vitro. Models of diabetic animals such as Goto-Kakizaki rats and models induced with streptozocin and alloxan were used. The hypoglycemic effects of leaf, seed, fruit and oil extracts were evaluated using isolated phytochemical compounds, tannins, flavonoids, alkaloids,saponins, terpenes and oleic acid. Studies have shown a consistent reduction in bloodglucose with the use of P. americana extracts by different pathophysiological pathways. Conclusion: The in vitro and in vivo studies showed that P. americana can contribute to the reduction of DM control, being a precursor of new substances with defined pharmacological activity and with great potential to transform a future antidiabetic drug. More comprehensive studies of the P. americana species are needed to significantly expand the understanding of the molecular mechanisms of action of its phytochemicals for the control of diabetes. Keywords: